Investment in the new Cuban tourist industry : a guide to entrepreneurial opportunities - Miller, Mark M. (Mark Michael), 1957- (Quorum Books, 1997)
Miller and Henthorne give U.S. investors and entrepreneurs the insights they need to capitalize upon the rapidly expanding, but still open, Cuban tourism industry - the island's major industry. This authoritative examination of the market for Cuban tourism provides comprehensive information on Cuban contacts and data sources that are accessible to foreigners; insights into the competition and possible competitive strategies, plus the general background on Cuba and its economy that investors must have for an understanding of Cuba's potential. With its lists of references and contacts, Miller and Henthorne's study will be invaluable to international tourism executives, particularly specialists in strategic planning and the development of strategic business alliances as well as international marketers and business development officers.